Pengaruh Kepuasan Kerja Dan Modal Psikologi Terhadap Komitmen Organisasional Pada PT. BPR Sukawati Pancasakti Bali: The Influence of Job Satisfaction and Psychological Capital on Organizational Commitment at PT. BPR Sukawati Pancasakti Bali - I Nyoman Hendra Laksmana (Jurnal Manajemen Bisnis Era Digital, 2024)
The aim of this research is to examine the influence of job satisfaction and psychological capital on organizational commitment at PT. BPR Sukawati Pancasakti Bali. The number of samples used in this research was 60 respondents which was determined using the Slovin formula. The data analysis methods used are validity and reliability tests, classical assumption tests, and multiple linear regression tests. The results of the research show that partially and/or simultaneously job satisfaction and psychological capital have a significant effect on organizational commitment at PT. BPR Sukawati Pancasakti Bali.